Biomarkers in cancer: an overview - Seow, Heng Fong (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2008)
Traditional tumour markers such as carcinoembryonic antigen (CEA) that have been used for screening gastrointestinal neoplasia for many years are not specific. However, these markers are useful after diagnosis to monitor progress of the disease and recurrence. New biomarkers are constantly being developed to identify individuals with risk of cancer for early detection, to determine prognosis, to detect recurrence, to predict drug responses and to monitor response to treatment. There are several issues involved in the discovery of biomarkers and their development for clinical applications. This article provides a basic overview of the classes of biomarkers, the current status of molecular profiling and discusses the opportunities as well as challenges ahead to improve biomarker development.